IMAGING CASE - Vieira, Maria João; Ferreira, Carla; Soares, Susana (BIRTH AND GROWTH MEDICAL JOURNAL, 2017)
A ten-year-old girl presented with a one week history of left knee pain, exacerbated by movement. She practiced handball regularly, but denied any recent trauma. There was no fever, night pain, fatigue or other constitutional symptoms. Physical examination revealed swelling and tenderness over the tibial tuberosity without erythema or warmth. Knee radiograph showed soft-tissue edema and fragmentation of the tibial tuberosity, findings consistent with Osgood-Schlatter disease. Osgood-Schlatter disease is an overuse injury caused by repetitive strain and chronic avulsion of the secondary ossification center (apophysis) of the tibial tuberosity. It is associated with growth spurts in physically active adolescents. The patient was treated with anti-inflammatories and rest during one week and gradually returned to activity. There was no recurrence during the two years follow-up.